Renal cell carcinoma in the ectopic kidney prospects of diagnosting and treatment of the carcinoma of the kidney - Brenčič, Erika (Radiology and oncology (Ljubljana), 2000)
Background. An extensive use of ultrasonography and computed tomography have enormously contributed to the early detection of adenocarcinoma of kidney taking into consideration that they have been so far often detected by chance.In addition to provide us with an image of a tumor and contributing to define more easily the nature of tumor, MRI is most helpful in detecting the infiltrations of tumor into its surroundings and changes in the veins. Case report. This case report presents the patient with adenocarcinoma of the ectopic kidney. The ultrasonography, computed tomography and magnetic resonance imaging detected and abundant non-homogenous tumor mass in pelvis minor. Additionally to the suspected ectopia of one of the kidney, it was alsosuspected that there was another pathological process of different etiology too. This suspicion was based on the detection of a different tumor mass in between the intestinal loops. Two months after the nonradical excisionof the adenocarcinoma from the ectopic kidney, the following changes were observed: progress of the residual tumor in the pelvis minor and the tumor in between the intestinal loops (that was not removed during the first operation). The patient was given immunochemotherapy and local radiotherapy. Conclusions. According to the available data in literature, the localization of tumor in ectopic kidney is extremely rare.
Keywords: Adult; Carcinoma, renal cell; Diagnosis; diagnostika; Kidney neoplasms; ledvice; Magnetic resonance imaging; Neoplasm invasiveness; Neoplasm metastasis; Prognosis; rak (medicina); Surgery; Survival analysis; Tomography, X-ray computed; Ultrasonography; zdravljenje